2021
DOI: 10.1097/ppo.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

Development of Next-Generation Poly(ADP-Ribose) Polymerase 1–Selective Inhibitors

Abstract: Poly(ADP-ribose) polymerase (PARP) inhibitors have transformed the therapeutic landscape for advanced ovarian cancer and expanded treatment options for other tumor types, including breast, pancreas, and prostate cancer. Yet, despite the success of PARP inhibitors in our current therapeutic armamentarium, not all patients benefit because of primary resistance, whereas different acquired resistance mechanisms can lead to disease progression on therapy. In addition, the toxicity profile of PARP inhibitors, primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Toxicity could be overcome through better formulation strategies, such as a nanoparticle formulation of talazoparib, which was effective in reducing toxicity in xenografts with Ewing sarcoma [ 5 ]. In the future, discovery of next-generation selective PARP inhibitors, such as AZD5305, which is currently in clinical development, will further improve the pharmacologic profile and reduce adverse effects [ 29 ]. These options could be considered in the design of future animal model studies.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity could be overcome through better formulation strategies, such as a nanoparticle formulation of talazoparib, which was effective in reducing toxicity in xenografts with Ewing sarcoma [ 5 ]. In the future, discovery of next-generation selective PARP inhibitors, such as AZD5305, which is currently in clinical development, will further improve the pharmacologic profile and reduce adverse effects [ 29 ]. These options could be considered in the design of future animal model studies.…”
Section: Discussionmentioning
confidence: 99%
“…First, improvement of the efficacy and safety of the combined therapy requires further evaluation in the future clinical studies, aiming to enhance the efficiency and decrease the chances of toxic adverse effects. For example, the development of selective PARPi in preclinical studies have demonstrated higher potency which may provide better clinical efficacy and broader spectrum of treatment [ 105 , 106 ]. Second, it is critical to screen and target the patient groups that benefit the most from the combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical benefits of PARP inhibitors have been proved, safety issues such as hematological toxicity need to be addressed ( Farres et al, 2013 ; LaFargue et al, 2019 ). The next generation of PARP inhibitors is under development, targeting selective PARP1, to remedy the adverse events caused by inhibition of PARP2 ( Curtin and Szabo, 2020 ; Dias et al, 2021 ; Johannes et al, 2021 ; Ngoi et al, 2021 ). Secondly, the PK characteristics of YHP-836 did not support its further development.…”
Section: Discussionmentioning
confidence: 99%